3D transient CFD modelling of a scroll-type hydrogen pump used in FCVs. (11th October 2018) - Zhang, Qingqing; Feng, Jianmei; Wen, Jie; Peng, Xueyuan
Abstract: The scroll pump has a great potential to recirculate hydrogen in a fuel-cell vehicle (FCV) because of its high efficiency, low noise and vibration, reliable operation, and a wide range of adjustable flow. This paper presents three-dimensional transient computational fluid dynamics (CFD) modelling of a scroll-type hydrogen pump used in FCVs, including leakage flow through both the radial clearance (RC) and axial clearance (AC). A dynamic mesh was generated for the moving orbiting scroll, and high-quality hexahedral structured grids with sufficient grid-density were applied to the clearances to solve the multi-scale problem. The pressure and velocity fields were obtained at different rotating angles to reveal the dynamic characteristics in the compression chambers. The simulation results showed that the radial leakage through AC has more significant influence on the volumetric efficiency than the tangential leakage through RC, especially on scroll-type hydrogen pumps. The presented modelling and simulation methods were validated experimentally by operating a scroll air compressor at different speeds and pressure ratios. The volumetric efficiency of the scroll pump was 85.39% with 0.02 mm AC and 0.02 mm RC, 81.43% with 0.02 mm AC and 0.04 mm RC, and 70.17% with 0.04 mm AC and 0.02 mm RC. Further, it was found that the performance of scroll-type hydrogen pumps is more sensitive to rotating speed than air scroll pumps under the same conditions. With hydrogen, the volumetric efficiency increased by 30.68% when the rotating speed was increased from 3000 r·min −1 to 6000 r·min −1 ; with air, the volumetric efficiency increased by 12.81%. Therefore, it is necessary to consider both AC and RC in the CFD modelling of scroll machines, particularly in the case of hydrogen scroll pumps. Highlights: 3D transient CFD numerical simulation with dynamic meshing was presented. Sufficient grid-density mesh was obtained in multi-scale fluid domains. The dynamic pressure and velocity fields at different angles were obtained. Leakage characteristics of the radial clearance and axial clearance were revealed.